Animal personality: a comparison of standardized assays and focal observations in North American red squirrels. (August 2022) - Martinig, A.R.; Karst, H.J.; Siracusa, E.R.; Studd, E.K.; McAdam, A.G.; Dantzer, B.; Delaney, D.M.; Lane, J.E.; Pokharel, P.; Boutin, S.
Abstract : As interest in animal personality research grows, methodologies for quantifying consistent among-individual differences in behaviour are expanding. Two of the most common methods for quantifying animal personality are standardized behavioural assays and focal animal sampling. We evaluated whether assays and focals provided similar animal personality measures in a wild population of free-ranging North American red squirrels, Tamiasciurus hudsonicus, by comparing the among-individual correlations of traits between methods. Assays described two behavioural axes—one associated with movement behaviours and another associated with antagonistic behaviours towards conspecifics. Focals described two additional behavioural axes—one associated with movement and territorial behaviours, and another associated with the trade-off between vigilant and feeding behaviours. Although we found evidence of high trait repeatability for behavioural axes measured with assays, both focal behavioural axes had low trait repeatability regardless of whether among-individual differences in the social environment were controlled for (i.e. to account for 'pseudopersonality'). We also found no among-individual correlations between assay and focal behavioural axes. The lack of correlation between methods may be because the dominant axes of variation differ between methods or because of the low trait repeatability of focals due to high behavioural plasticity. Given this, we conclude that assays will likely remain the mainstay for measuring consistent among-individual differences in behaviour given their ability to standardize for environmental conditions. Highlights: We evaluated whether assay and focal observations measure similar behavioural axes. Assays captured behaviours associated with movement and antagonistic behaviour. Focals captured behaviours associated with territoriality and vigilance/feeding. We found no among-individual correlations between methodologies. Assays remain the mainstay for measuring personality by controlling for environment.